RESPON PERTUMBUHAN DAN PRODUKSI TANAMAN JAGUNG (Zea mays L.) VARIETAS JANTAN F1 TERHADAP BERBAGAI DOSIS PUPUK KOTORAN HEWAN YANG BERBEDA PADA MEDIA TAILING - Fitri Fitri; HM Saputra; D Pratama; SN Aini (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2022)
Post-tin mining areas dominated by sand tailings cause low nutrients and low water holding capacity. Application of animal waste on tailings medium will provide nutrients and help to increase water holding capacity. The purpose of this study was to determine the dose and type of animal waste that can improve the growth and yield of corn in tailings medium. This research was conducted from January to May 2021 at Experimental and Research Field (KP2), Faculty of Agriculture, Fisheries and Biology, University of Bangka Belitung. The study used a single factor randomized block design with five replicates. This study consisted of four levels of treatment there were sand tailings and cow waste 10 t ha-1 (MS1), tailings sand and cow waste 20 t ha-1 (MS2), tailings sand and chicken waste 10 t ha-1 (MA1), tailings sand and chicken waste 20 t ha-1 (MA2). Results showed that different doses and types significant affected the growth and yield of corn in tailings medium. A dose of 20 t chicken waste ha-1 showed the best growth and yield on F1 male cultivar of corn.